Gerakan politik Melayu, 1945-1957 - Ramlah Adam (Kangar : Penerbit Universiti Malaysia Perlis, 2013)
On history, politics and government since 1945-1957 in Malaya.
Includes bibliographical references (page 366-376) and index.
In Malay.
Keywords: Malays -- Politics and government; Political parties -- Malaysia -- History; Malaysia -- Politics and government